Family Aggregation of HTLV-1 Infection Associated with FAS -670A/G Polymorphism: A Case Report - Vallinoto, Antonio C. R.; Santana, Bárbara B.; Queiroz, Maria A. F.; da Silva, Andrea N. M. R.; Cayres-Vallinoto, Izaura M. V.; da Costa, Carlos A.; de Sousa, Maisa S.; Ishak, Ricardo (Frontiers in Microbiology, 2018)
Human T-lymphotropic virus 1 (HTLV-1) infection has been associated with ATL and inflammatory diseases but remains a neglected health problem. HTLV-1 associated diseases were originally described as sporadic entities, but family aggregations have been reported. Viral, genetic, immunological and behavioral factors were used to explain family clusters, but until now a clear explanation remains uncertain. In the present study we report, for the first time, a family cluster of diseased persons presenting the infection across three generations associated with FAS -670A/G polymorphism.